2018
DOI: 10.5551/jat.43240
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Imaging Characteristics of Cerebral Infarction in Patients with Nonvalvular Atrial Fibrillation Combined with Cerebral Artery Stenosis

Abstract: Aims: Nonvalvular atrial fibrillation often occurs in combination with carotid atherosclerosis, but less is known about it in combination with cerebral artery stenosis. This study investigated the characteristics of cerebral infarction in patients with nonvalvular atrial fibrillation with or without cerebral artery stenosis. 13.3%) were higher in the stenosis group (n 107) than in the non-stenosis group (n 65) (P 0.01). In the stenosis group, there were different types of cerebral infarction lesions, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
(30 reference statements)
3
20
0
Order By: Relevance
“…This further reduces cerebral blood flow, and causes the insufficiency of blood supply for brain tissues, aggravating the cerebral infarction. This conclusion is basically consistent with the results reported in literature (13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This further reduces cerebral blood flow, and causes the insufficiency of blood supply for brain tissues, aggravating the cerebral infarction. This conclusion is basically consistent with the results reported in literature (13)(14)(15)(16).…”
Section: Discussionsupporting
confidence: 94%
“…Cerebral artery stenosis is another risk factor for progressive cerebral infarction (14). Zhiwu Wu et al (17) reported that the risk of severe cerebral infarction increased in patients with severe cerebral artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…At present, imaging technology is mainly used to diagnose and treat patients with cerebral infarction. Compared with X-ray and computed tomography (CT) scanning technology, MRI has clearer scan images and relatively low ionizing radiation, so it is often used in the diagnosis and treatment of patients with cerebral infarction [ 2 ]. However, MRI technology still has some shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…as hypertension, AS, dyslipidaemia, obesity, diabetes mellitus, and smoking (6)(7)(8). Hypertension is an important traditional risk factor in the progression of cerebral infarction (9).…”
Section: The Development and Progression Of Cerebral Infarction Are Amentioning
confidence: 99%